A Multi-Object Grasp Technique for Placement of Objects in Virtual Reality - Unai J. Fernández; Sonia Elizondo; Naroa Iriarte; Rafael Morales; Amalia Ortiz; Sebastian Marichal; Oscar Ardaiz; Asier Marzo (Applied Sciences, 2022)
Some daily tasks involve grasping multiple objects in one hand and releasing them in a determined order, for example laying out a surgical table or distributing items on shelves. For training these tasks in Virtual Reality (VR), there is no technique for allowing users to grasp multiple objects in one hand in a realistic way, and it is not known if such a technique would benefit user experience. Here, we design a multi-object grasp technique that enables users to grasp multiple objects in one hand and release them in a controlled way. We tested an object placement task under three conditions: real life, VR with single-object grasp and VR with multi-object grasp. Task completion time, distance travelled by the hands and subjective experience were measured in three scenarios: sitting in front of a desktop table, standing up in front of shelves and a room-size scenario where walking was required. Results show that the performance in a real environment is better than in Virtual Reality, both for single-object and multi-object grasping. The single-object technique performs better than the multi-object, except for the room scenario, where multi-object leads to less distance travelled and reported physical demand. For use cases where the distances are small (i.e., desktop scenario), single-object grasp is simpler and easier to understand. For larger scenarios, the multi-object grasp technique represents a good option that can be considered by other application designers.